Chaos Based Cryptography An Alternative to Algebraic Cryptography - Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, 2008)
In this paper we will first discuss cryptography from a historical point of view in order to understand the motivation behind this science. We will discuss the earliest form of cryptography before fast forwarding to the current modem forms of cryptography. We will then mention issues surrounding current modem cryptographic methods before introducing chaos based cryptography. The relationship between chaos and cryptography makes it natural to employ chaotic systems to design new cryptosystems. It is based on the facts that chaotic signals are usually noise-like and chaotic systems are very sensitive to initial conditions. Their sensitivity to initial conditions and their spreading out of trajectories over the whole interval seems to be a model that satisfies the classic Shannon requirements of confusion and diffusion [1] From 1989 onwards, many different chaotic encryption systems have been proposed. The most celebrated chaotic cryptosystem is based on the ergodicity property of chaotic maps [2] and has received more and more attentions in the past literature [3-17]. Introduced by Baptista in 1998, it is able to produce different ciphers for the same plaintext. It was cracked by Alvarez in 2003 via the one-time pad attack. In 2008, M.R.K.Ariffin and M.S.M.Noorani [22] engaged the attack and devised a counter measure against it.